Sustainable Architecture and Food Production: Impact of Modernity on the Traditional Urban Form. (2010)
Architecture in any period has often been a reflection of the sociological, cultural, economic and technological aspects of its development. Though it has been argued that Africa has no recorded history in the written form, but evidences persist of the rich culture of the different tribes that makes up the constituent of its inhabitants. This paper examines some of these socio-cultural factors that impinge on the historical traditional forms and architectural system in sub-Saharan Africa, by considering the pattern of food production and consumption. It also examines in particular existing relationship between architecture and food consumption that affect the sustainable built form found in southwest Nigeria. The paper is thus an endeavor to discuss the connections, interrelationships and benefits of these concepts in the evolving modem sociocultural views on Africa. The paper report a recent field survey carried out in the study area, based on quantitative and qualitative methodology. Sizeable numbers of questionnaire are administered to the target population, using stratified random sampling method in order to elicit primary data with 76 percent response rate from the respondent. The survey and interview conducted highlights a number of observations and conclusion of the relationship between food production activities and its role in city development or formation.